Modelling, simulation and optimal design of a TCSC-based controller in a power system. (2nd February 2010) - Panda, Sidhartha; Sahu, Rabindra Kumar
This paper presents a MATLAB/Simulink-based modelling and simulation of a power system installed with a thyristor controlled series compensator (TCSC)-based controller which is suitable for carrying out power system stability studies. The synchronous generator is represented by one field circuit and one equivalent damper on q-axis known as the Model 1.1, so that the impact of TCSC on power system stability can be more reasonably evaluated. Further, a TCSC-based controller has been designed for improving the system damping. The design problem of the proposed controller is formulated as an optimisation problem and differential evolution (DE) optimisation technique is employed to search for the optimal controller parameters. A detailed analysis on the selection of control signals, both local (line current) and remote (speed deviation) signals, on the effectiveness of the TCSC controller is carried out and simulation results are presented.